Intestinal perforation after surgical treatment for incisional hernia: iatrogenic or idiopathic?. Issue 1 (1st January 2018) - Amorosi, V.; Longo, B.; Sorotos, M.; Firmani, G.; D'Angelo, F.; Santanelli di Pompeo, F.
Abstract: Intestinal perforation (IP) is a life-threatening gastroenterological condition requiring urgent surgical care, which may present itself as an uncommon complication following incisional hernia repair surgery, most often because of iatrogenic traumatism occurring during the procedure. However, we report a case where a spontaneous onset can be hypothesised. A 60-years-old patient underwent repair of an abdominal laparocele, through rectus abdominis muscle plasty, 5 years after development of an incisional hernia due to exploratory laparotomy for the treatment of acute appendicitis. Xipho-pubic scar was excised and umbilicus and supra-umbilical hernia sac dissected, a linear median incision was performed along the sub-umbilical linea alba, reaching preperitoneal plane to assess any intestinal loop adherence to the abdominal wall. After limited viscerolysis, abdominal wall defect was corrected by 'rectus abdominis muscle plasty' and umbilicus reconstruction by Santanelli technique. Postoperative course was uneventful until Day 29, with sudden onset of epigastric pain, fever and bulge. Sixty cubic centimeter pus was drained percutaneously and cavity was rinsed with a 50% H2O2 and H2O V-V solution until draining clear fluid. Symptoms recurred two days later, while during rinsing presented dyspnoea. X-Ray and CT scan diagnosed IP, and she underwent under emergency an exploratory laparotomy, leading to right hemicolectomy extended to last ileal loops and middle third of the transverse, right monolateral salpingo-ovariectomy and a temporary ileostomy by general surgeon. Twenty-three days later an ileostomy reversal surgery was performed and 8 days after she was discharged. At latest follow-up patient showed fair conditions, complaining abdominal pain and diarrhoea, attributable to the extensive intestinal resection. IP following incisional hernia repair, is reported as uncommon and early postoperative complication. In our case, the previous regular postoperative course with late onset lead us to hypothesise a possible idiopathic etiopathogenesis, because of a strangulation followed by gangrene and abscess formation, which might begin before the incisional hernia repair and unnoticed at the time surgery was performed.